2021
DOI: 10.3389/fimmu.2021.658843
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte-Related Immunological Indicators for Stratifying Mycobacterium tuberculosis Infection

Abstract: BackgroundEasily accessible tools that reliably stratify Mycobacterium tuberculosis (MTB) infection are needed to facilitate the improvement of clinical management. The current study attempts to reveal lymphocyte-related immune characteristics of active tuberculosis (ATB) patients and establish immunodiagnostic model for discriminating ATB from latent tuberculosis infection (LTBI) and healthy controls (HC).MethodsA total of 171 subjects consisted of 54 ATB, 57 LTBI, and 60 HC were consecutively recruited at To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Results from blood examination, biochemical tests, coagulation detection, and T-SPOT assay showed mediocre value in identifying Mtb infection status [ 18 , 19 ]. In addition, the value of the detection targeting lymphocyte number and function for TB diagnostics was also confirmed by two recent reports [ 20 , 21 ]. Although these tests were of limited discriminatory value when they were used separately, the diagnostic performance of these data could be effectively improved when the data is integrated with appropriate algorithm.…”
Section: Introductionsupporting
confidence: 60%
“…Results from blood examination, biochemical tests, coagulation detection, and T-SPOT assay showed mediocre value in identifying Mtb infection status [ 18 , 19 ]. In addition, the value of the detection targeting lymphocyte number and function for TB diagnostics was also confirmed by two recent reports [ 20 , 21 ]. Although these tests were of limited discriminatory value when they were used separately, the diagnostic performance of these data could be effectively improved when the data is integrated with appropriate algorithm.…”
Section: Introductionsupporting
confidence: 60%
“…Although many advances have been achieved, especially in omics field (60-62), there were some practical limitations for their clinical application, including expensive laboratory facilities and sophisticated operating procedures. Meanwhile, immunodiagnostics has received considerable attention as an alternative for discrimination of MTB infection status in recent years (63)(64)(65)(66)(67)(68)(69)(70). Nevertheless, the identified biomarkers including proteins and cytokines in serum or plasma for diagnostic aim may not be specific for TB due to the influence brought by other immune related diseases such as infection and autoimmune diseases (71)(72)(73)(74)(75)(76)(77).…”
Section: Discussionmentioning
confidence: 99%
“…The active TB patients included in this study had lymphopenia, which was caused by reduced numbers of Th cells, Tγδ cells, and ILC1s. Previous studies have reported reduced numbers of these three lymphocyte subsets in active TB patients 13,45–47 . The decreased numbers of peripheral blood lymphocytes in active TB patients could be caused by migration of these cells to the infected organs, the lungs.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have reported reduced numbers of these three lymphocyte subsets in active TB patients. 13,[45][46][47] The decreased numbers of peripheral blood lymphocytes in active TB patients could be caused by migration of these cells to the infected organs, the lungs. In the BAL cell suspensions from the active TB patients included in this study, ILC1s were the most abundant ILC subset, which is consistent with reports that intranasal immunization of mice with M. bovis BCG, 12 or with a subunit vaccine against Mtb (ESAT-6 with c-di-AMP as an adjuvant), 48 increases the number of ILC1s in mice lungs.…”
Section: Discussionmentioning
confidence: 99%